Práticas cotidianas e processos de territorialização: um estudo com jovens trabalhadores - Alice Gerlane Cardoso da Silva (2022)
In this thesis dissertation, I aimed to understand how daily life practices occur in the process of territorialization of spaces experienced by young workers from their insertion at IESP. I was theoretically based on Certeau (1994), Certeau, Giard and Mayol (1996) and Raffestin (1993), considering that it is through the individual actions, whether as tactics, strategy or convenience, that the territorialization process takes place. In other words, daily life is not just about mere routine and standardized situations. It is a disordered composition of daily practices of freedom, whether of obedience or insubordination, expressed in every gesture and sometimes imperceptible to the forces of control. Territorialization, in turn, is understood as a complex, systematic and non-linear process, which happens when the subject appropriates a space, either in a concrete or abstract way. Therefore, in this research I discuss the practices of the individuals (CERTEAU, 1994) that occur in the territorial system (RAFFESTIN, 1993) and that cause the processes of territorialization of young workers and, consequently, territoriality. The ordinary man, in this study, is represented by the young (poor) worker. Therefore, through a qualitative research, I carried out participant observation and thematic oral history interviews with 22 young workers in February 2019. To interpret the collected data, I used narrative analysis. In general, the analysis suggests that different practices are undertaken by young workers in order to maintain their coexistence in such spaces, thus constituting territories in which they act and react in their daily lives. Such practices are configured as small tricks and can be tactical or convenience. They were apprehended at the IESP and have characteristics of accommodation or creative, emancipatory aspects. Thus, young workers act in the territorial system, made up of textures, nodes and networks, through practices and power relations and, thus, build a territoriality, a phenomenon that both causes and results from territorialization. Finally, I conclude that young workers end up replicating the silent and almost invisible operations that they carry out in the territory of the IESP and, for that purpose, they use the same cunning to operate in the fissures of the mechanisms present in other spaces, as a way of resisting what is imposed.